Optimizing Cultural Heritage Use in Regional Tourism and Hospitality Development (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The given study evaluates methodological breakthrough in the context of a more successful implementation of the resources of cultural heritage in the development of the tourism and hospitality industry in Uzbekistan with the focus on the cultural assets that are not used properly by that country. Even though the nation can boast a rich body of historical monuments, traditions, and architectural sites, there is still a severe deficit in the integration of those resources into sustainable tourism models. Based on a qualitative-descriptive approach, the researcher examines discourse in the field of academic works and policy about the development of regional tourism. Empirical data shows that the lack of infrastructure, contentious planning as well as inadequate community participation are some of the challenges hampering the optimum use of cultural heritage in tourism. The research, thus, proposes strategicizing measures, such as inclusive procession of governance, digitalisation of heritage-related information, and tourism modeling that is locally situated. The implications mean that a synthesis between heritage preservation and tourism growth could enhance regional development, strengthen the community empowerment and raise the competitiveness of the Uzbekistan to the international level.